A letter from the Prince of Viana - Bravo Lledó, Pilar (Huarte de San Juan. Geografía e Historia, 2009)
The author publishes a letter from Charles de Viana sent to the abbot of Poblet, by means of which he informed him that he had chosed the candidate for the beggar’s position, friar Joan de Vinyoles.